The THE USE OF SIMULATED ANALOG CLOCKS TO IMPROVE TIME-READING SKILLS IN MATHEMATICS LEARNING FOR SECOND-GRADE STUDENTS AT SDIT ARRAUDHOH - Sarifah Zahra Zahra; Khairany Siti Kamilah (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2026)
The low ability of second-grade elementary students at SDIT Ar Raudhoh in reading analog clocks is caused by abstract mathematics instruction and limited use of concrete learning media, which creates a gap between learning needs and classroom practice. This study aimed to improve students’ ability to read time using an analog clock model through a Hands-On Learning approach. The research used Classroom Action Research based on the Kemmis and McTaggart model, conducted in two cycles involving 12 students. Data were collected through observation and learning achievement tests. The results showed a significant improvement in students’ learning outcomes. The percentage of mastery increased from 16.7% in the pre-cycle stage to 41.7% in Cycle I, and reached 91.7% in Cycle II with an average score of 89.2. These findings indicate that the use of a student-made analog clock model effectively helps students understand the concept of time in a more concrete and meaningful way. The improvement also reflects higher student engagement and motivation during learning activities. This study contributes to mathematics education by providing an alternative practical learning strategy that supports early-grade students’ conceptual understanding of time and can be applied by teachers to improve learning quality in elementary schools.